Is deflation a threat to growth? : - Borisova, Anastasiia (2020)
The work is aimed at finding an answer to the question posed: "Is deflation a threat to growth?" The European Union economic market after the crisis of 2008-2009 is analyzed for the threat of deflation to economic growth. The analysis is based on the wide theoretical base of many famous economists. The evolutionary path of the development of the deflation phenomenon was traced, starting with the first systematic analysis by David Hume, an analysis of scholars of the classical economic school, John Maynard Keynes, Irving Fisher and many other scientists who showed and explained the effects of this phenomenon. The paper analyzes historical examples of deflation in different countries, suggests ways to combat deflation.The practical part is based on the analysis of many macro-indicators: the level of investment, inflation, GDP growth, the situation on the labor market the level of deflation available through the activities of Eurostat, World Bank and International Monetary Fund. Special attention was paid to inflation expectations and the program of the Central Bank. The author of the work provides his point of view on the economic situation in the market in the conditions of the recession and 2020 and gives forecasts and prospects for the development of the European Union.